PEMAHAMAN PENDERITA DIABETES MELITUS DALAM UPAYA MENCEGAH TERJADINYA KOMPLIKASI ULKUS DIABETIK - Iswadi (SCIENTIA JOURNAL, 2021)
One of the priorities of Indonesia's health development is to extend life expectancy by reducing the number of degenerative diseases. Degenerative disease is a chronic chronic disease that affects a person's quality of life and productivity, including diabetes mellitus. Diabetes mellitus is a disease that we often encounter in the community because of its high mortality rate, besides that this disease also has a high impact on complications for patients such as diabetic ulcers, so that various efforts to prevent complications of diabetic ulcers must be understood by patients.The purpose of this study to obtain information on the understanding of people with diabetes mellitus in an effort to prevent complications of diabetic ulcers. Methods the study was conducted using a qualitative approach that was presented descriptively, both primary data and secondary data in one of the Puskesmas working areas in Jambi City in 2016. Primary data was obtained through questionnaires to a sample of 33 respondents, while secondary data was by reviewing medical record documents of respondents' visits. The results of the study showed that most of the 19 respondents (57.6%) had a good understanding, and 14 respondents (42.4%) had a poor understanding of preventing complications of diabetic ulcers. From the results of the study it can be understanding of people with diabetes mellitus in preventing complications of diabetic ulcers is good, but the percentage is still low, because there are still several components of efforts to prevent complications of diabetic ulcers that respondents do not understand.